PENGARUH PEMBERIAN PERAWATAN STEAM CURING TERHADAP KEKUATAN DAN DURABILITAS BETON DENGAN SEMEN POZZOLAN (EFFECT OF STEAM CURING ON STRENGTH AND DURABILITY CONCRETE WITH CEMENT POZZOLAN) - Rommel, Erwin (Media Teknik Sipil, 2011)
The use of concrete as a building material has been developed both in quantity and qualityaspects. Concrete production time is long term in a foundry to make many breakthroughs to makea concrete material that fast food, such as precast concrete. The use of precast concrete in the areaof an aggressive environment than expected strength factors are also needed high durability,including resistance to porosity and permeability properties of concrete.This research was conducted with the cooperation of one of Precast Concrete Factory in EastJava, including the manufacture of 15x15x15 cm cube of concrete and steam curing system.Thisvariable on research ; use the type of cement (pozzolan cement and cement type-1), the length ofsteam (5 and 7 hours), and the quality concrete (K350 and K700). As for the testing performed oncompressive strength, permeability and porosity of concrete.This study concluded that steam curing system to provide early strength concrete that isbetter than conventional curing (non-steam), where compressive strength of the post-steam canreach 51% of high-strength concrete (K700) with the results 361 kg/cm2, whereas in normalconcrete (K350) reached 52% (compressive strength 192 kg/cm2). Pozzolan cement concrete alsohas the advantage in increasing the durability of concrete, especially in high-strength concrete,where the concrete porosity becomes smaller either by steam curing and non-steam. Permeabilityof concrete is given a steam becomes smaller than the normal concrete with conventional curing(non-steam).Key word : steam curing, pozzolan cement, strength of concrete